Girl online : going solo - Sugg, Zoe (New York : Keywords Press, 2016)
Penny's life is back to normal. As Penny starts the school year she's ready to face the world--alone. Noah has gone off the radar after ending his world tour early, and no one, including Penny, knows where he is. So when she accepts Megan's invitation to visit her performing arts school, it seems like an opportunity to make some new friends. Helping everyone else seems to be the right remedy--Elliot needs her friendship more than ever, and she meets Posey, who she can really help with her stage fright. But is charming Scottish boy Callum the right kind of distraction? And can Penny truly move on when Noah's shadow seems to haunt her around every corner?
Keywords: Blogs -- Fiction; Love stories